Switchable Pickering emulsions stabilized by silica nanoparticles hydrophobized in situ with a conventional cationic surfactant - Zhu, Yue (Langmuir : the ACS journal of surfaces and colloids, 2015)
A stable oil-in-water Pickering emulsion stabilized by negatively charged silica nanoparticles hydrophobized in situ with a trace amount of a conventional cationic surfactant can be rendered unstable on addition of an equimolar amount of an anionic surfactant. The emulsion can be subsequently restabilized by adding a similar trace amount of cationic surfactant along with rehomogenization. This destabilization-stabilization behavior can be cycled many times, demonstrating that the Pickering emulsion is switchable. The trigger is the stronger electrostatic interaction between the oppositely charged ionic surfactants compared with that between the cationic surfactant and the (initially) negatively charged particle surfaces. The cationic surfactant prefers to form ion pairs with the added anionic surfactant and thus desorbs from particle surfaces rendering them surface-inactive. This access to switchable Pickering emulsions is easier than those employing switchable surfactants, polymers, or surface-active particles, avoiding both the complicated synthesis and the stringent switching conditions